Analisis Pendapatan dan Efisiensi Pemasaran Kepiting Bakau di Kecamatan Seruway Kabupaten Aceh Tamiang - Evi Ramadhani Parapat; Abdurrachman (Jurnal Penelitian Agrisamudra, 2019)
The aim of this research to know mangrove crab farmer profit, marketing channel, marketing margin and efficiency of mangrove crab. This research did in Seruway sub-district, Aceh Tamiang district. Sample of this research are 30 farmer consist of 10 farmers from Lubuk Damar village, 20 farmers from Sungai Kuruk III village and 8 sample trader consist of 7 collectors and 1 wholesaler. The result showed that the profit is Rp. 2.226.140/Ha. There is 2 marketing channel of mangrove crab. The average cost of marketing on the channel I is Rp. 24.590/Kg and channel II is Rp. 6.091/Kg. marketing efficiency of mangrove crab in channel I is 5,75% and in channel, II is 1,31%